Strategies for Dealing with Difficult Situations - Dr. Walter H. Gmelch (Academic Chairpersons Conference Proceedings, 2018)
The session will give ideas and strategies for handling difficult conversations with deans, fellow chairs, and faculty. Using case studies and role plays, the session will engage participants to address the following questions and challenges: How do I manage my dean? What are guidelines for handing complaints? What styles are most appropriate in handling difficult situations? How can chairs become more “principled” in resolving differences? What are personal strategies for dealing with difficult colleagues?
Keywords: Strategies Difficult Situations Faculty Dealing